2020
DOI: 10.33988/auvfd.666779
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Pasteurella multocida isolates recovered from the oral flora of cats

Abstract: In this study, it was aimed to investigate the presence of Pasteurella multocida in the swab samples taken from the oral cavity of cats, and to determine the capsular type and antimicrobial susceptibility of the isolates. For this purpose, swab samples taken from 300 cats were inoculated onto Knight's selective enriched medium and blood agar for isolation of P. multocida. Following after capsular typing of the isolates by PCR, the susceptibilities of the isolates to ceftiofur, clindamycin, erythromycin, enrofl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Several studies have shown that certain genes contribute to infection success [7] and encode the biosynthesis of key structural and metabolic molecules [8][9][10] required for adhesion, iron acquisition, colonization, immune response evasion, and survival in the host. Other researchers have identified important non-genetic factors involved in their pathogenesis; for instance, this microorganism is normally found in the oropharyngeal cavity [11][12][13], and immunological failures attributable to coinfections, environmental changes, or zootechnical stress are observed [14].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that certain genes contribute to infection success [7] and encode the biosynthesis of key structural and metabolic molecules [8][9][10] required for adhesion, iron acquisition, colonization, immune response evasion, and survival in the host. Other researchers have identified important non-genetic factors involved in their pathogenesis; for instance, this microorganism is normally found in the oropharyngeal cavity [11][12][13], and immunological failures attributable to coinfections, environmental changes, or zootechnical stress are observed [14].…”
Section: Introductionmentioning
confidence: 99%